Cosmopolitanism and patriotism: questions of identity, membership and belonging - Silva, Elisabete Mendes (2011)
Must we choose between cosmopolitanism and patriotism or, as A. Kwame Appiah defends, can we be cosmopolitan patriots or rooted cosmopolitans? This paper’s main purpose is to reflect upon the similarities and differences of cosmopolitanism and patriotism, focussing on the problems of world citizenship and accounting for the role of local identities, nowadays.